2007
DOI: 10.1158/0008-5472.can-07-0139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of CCAAT/Enhancer Binding Protein α in Epidermis Reveals Its Role in Suppression of Epithelial Tumorigenesis

Abstract: CCAAT/enhancer binding protein A (C/EBPA) is a basic leucine zipper transcription factor that inhibits cell cycle progression and regulates differentiation in various cell types. C/EBPA is inactivated by mutation in acute myeloid leukemia (AML) and is considered a human tumor suppressor in AML. Although C/EBPA mutations have not been observed in malignancies other than AML, greatly diminished expression of C/EBPA occurs in numerous human epithelial cancers including lung, liver, endometrial, skin, and breast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…Abrogation of C/EBP␣ functions has also been reported in AML-ETO and BCR-ABL leukemias (36,38), and ectopic expression of C/EBP␣ induces the differentiation of such leukemic cells (53,54). Moreover, the loss of C/EBP␣ expression in the epidermis increases susceptibility to Rasinduced skin tumorigenesis (28), similarly to the overexpression of E2F1 or DP1 transgenes in the mouse (40,55). To further delineate the contribution of failure to activate terminal differentiation genes in tumorigenesis, it would be interesting to identify a DP mutant that retains E2F coregulation but is defective for C/EBP␣ interaction.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Abrogation of C/EBP␣ functions has also been reported in AML-ETO and BCR-ABL leukemias (36,38), and ectopic expression of C/EBP␣ induces the differentiation of such leukemic cells (53,54). Moreover, the loss of C/EBP␣ expression in the epidermis increases susceptibility to Rasinduced skin tumorigenesis (28), similarly to the overexpression of E2F1 or DP1 transgenes in the mouse (40,55). To further delineate the contribution of failure to activate terminal differentiation genes in tumorigenesis, it would be interesting to identify a DP mutant that retains E2F coregulation but is defective for C/EBP␣ interaction.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, C/EBP␣ and C/EBP␤ appear to be functionally distinct, as Sebastian and coworkers have shown that C/EBP␤ fails to repress E2F in an equivalent TKO cell line (46,48). It is known that despite their extended homology and partial redundancy (2,6,20), C/EBP␣ and C/EBP␤ may also have antagonistic functions, e.g., in the case of skin tumorigenesis, where the lack of C/EBP␣ promotes tumorigenesis (28), whereas the lack of C/EBP␤ protects against chemical-induced skin carcinogenesis (60). Curiously, pRB deficiency also protects from tumorigenesis in a murine skin carcinogenesis model (45).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas C/EBP-b-deficient mice had mild epidermal hyperplasia, epidermis-specific C/EBP-a-deficient mice showed no skin phenotypic abnormalities in steady state (Zhu et al 1999;Loomis et al 2007). Keratinocyte-specific ablation of both C/EBP-a and C/ EBP-b revealed hyperproliferation of basal kerationocytes and halted terminal differentiation (Lopez et al 2009).…”
Section: Transcription Factormentioning
confidence: 99%
“…A number of studies have indicated a role for C/EBPa in regulating proliferation in several organs, including the lung (Flodby et al 1996, Diehl 1998, Loomis et al 2007. Deletion and ectopic expression of C/EBPa in the lung have revealed a vital role in regulating proliferation also in the alveolar epithelium (Flodby et al 1996, Sugahara et al 2001, Basseres et al 2006, Berg et al 2006, Didon et al 2010.…”
Section: Function Of C/ebpamentioning
confidence: 99%